Clinical features and posttreatment monitoring of dogs administered rivaroxaban (2018–2020): 19 cases. Issue 5 (20th April 2022) - Tracy, Alyxandra L.; Goggs, Robert; Brooks, Marjory B.; Lynch, Alex M.
Abstract: Objective: To describe a population of sick dogs administered rivaroxaban monitored with a rivaroxaban‐calibrated anti‐Xa activity assay (aXa). Design: Descriptive retrospective study. Setting: Two veterinary teaching hospitals. Animals: Client‐owned dogs administered rivaroxaban and monitored with aXa from January 2018 to January 2020 were eligible for study. Interventions: None. Measurements and Main Results: Medical records were reviewed and 19 dogs with a variety of underlying disease processes were identified. Rivaroxaban was administered to 12 of 19 dogs (63%) with confirmed thrombosis, 4 of 19 dogs (21%) with a strong clinical suspicion of thrombosis, and in 3 of 19 dogs (16%) with no current evidence of thrombosis. The median rivaroxaban dose administered was 0.96 mg/kg/day (0.62–1.58 mg/kg/day), with 15 of 19 dogs (79%) receiving rivaroxaban once daily. Clopidogrel was concurrently administered to 11 of 19 dogs (58%). Complete or partial thrombus resolution was identified in 5 of 12 (42%) and 3 of 12 (25%) dogs, respectively. Rivaroxaban appeared safe, with only 1 of 19 dogs (5%), concurrently administered clopidogrel, developing evidence of mild hematuria. Posttreatment monitoring revealed that 8 of 19 dogs (42%) had aXa below the target (aXa range of 150–250 ng/ml associated with effective treatment and prevention of venous thrombosis in people). The remaining 3 to 19 dogs (16%) achieved this range, and 8 of 19 dogs (42%) exceeded the range. No significant relationship between the initial rivaroxaban dose administered and the corresponding aXa result was identified. There were also no significant differences in baseline clinicopathological variables in dogs in which aXa fell within or outside this range. Conclusions: aXa was most commonly measured in dogs receiving rivaroxaban with confirmed or suspected thrombosis. Dogs in this study received a range of rivaroxaban dosages and attained variable aXa values that were not directly correlated with dosage.